The Influence of Maternal Pragmatics on the Language Skills of Children with Autism. Issue 5 (June 2017) - Stern, Yael S.; Maltman, Nell; Roberts, Megan Y.
ABSTRACT: Objective: This study examined the relationship between mothers' pragmatics and child language in autism spectrum disorder (ASD) and non-ASD language delay (LD) mother-child dyads. Methods: Participants consisted of 20 dyads of mothers and their toddlers aged 24 to 48 months, with ASD (n = 10) or non-ASD LD (n = 10). Groups were matched on child chronological age, language, and cognition. Maternal pragmatic language was qualified based on the degree of pragmatic violations during a semistructured interview, and was examined in relation to both child language, as measured by the Preschool Language Scale-4 and maternal use of language facilitation strategies during play. Results: Lower rates of maternal pragmatic violations were associated with higher expressive language scores in children with ASD, and with higher receptive language scores for children with non-ASD LD. Within ASD dyads, maternal pragmatic violations were negatively related to mothers' use of linguistic expansions. Conclusion: These findings indicate that parental pragmatics likely contribute to early language learning, and that the effects of maternal pragmatics on early language in ASD may be indirect (e.g., through parents' use of facilitative strategies). Parent-mediated language interventions for ASD should therefore consider parent pragmatics, especially given that pragmatic differences have been identified in unaffected family members of individuals with ASD.